Comparative genomics of the Natural Killer Complex in carnivores - Futas, Jan; Jelinek, April L; Burger, Pamela A; Horin, Petr (Frontiers in immunology, 2024)
BACKGROUND: The mammalian Natural Killer Complex (NKC) harbors genes and gene families encoding a variety of C-type lectin-like proteins expressed on various immune cells. The NKC is a complex genomic region well-characterized in mice, humans and domestic animals. The major limitations of automatic annotation of the NKC in non-model animals include short-read based sequencing, methods of assembling highly homologous and repetitive sequences, orthologues missing from reference databases and weak expression. In this situation, manual annotations of complex genomic regions are necessary. METHODS: This study presents a manual annotation of the genomic structure of the NKC region in a high-quality reference genome of the domestic cat and compares it with other felid species and with representatives of other carnivore families. Reference genomes of Carnivora, irrespective of sequencing and assembly methods, were screened by BLAST to retrieve information on their killer cell lectin-like receptor (KLR) gene content. Phylogenetic analysis of in silico translated proteins of expanded subfamilies was carried out. RESULTS: The overall genomic structure of the NKC in Carnivora is rather conservative in terms of its C-type lectin receptor gene content. A novel KLRH-like gene subfamily (KLRL) was identified in all Carnivora and a novel KLRJ-like gene was annotated in the Mustelidae. In all six families studied, one subfamily (KLRC) expanded and experienced pseudogenization. The KLRH gene subfamily expanded in all carnivore families except the Canidae. The KLRL gene subfamily expanded in carnivore families except the Felidae and Canidae, and in the Canidae it eroded to fragments. CONCLUSIONS: Knowledge of the genomic structure and gene content of the NKC region is a prerequisite for accurate annotations of newly sequenced genomes, especially of endangered wildlife species. Identification of expressed genes, pseudogenes and gene fragments in the context of expanded gene families would allow the assessment of functionally important variability in particular species.
Keywords: Cats; Killer Cells, Natural; genomika; Lectins, C-Type; Natural Killer Complex; anotace sekvence; lektiny typu C; CLEC; Genome; kočky; Molecular Sequence Annotation; Felids; Carnivora; zvířata; Genomics; fylogeneze; genom; genomes; carnivore; KLR; buňky NK; Phylogeny; Animals